Analisis Waktu dan Biaya Penyelesaian Proyek Transmisi 150 kV Dengan Pendekatan Critical Path Method dan Time Cost Trade Off - Muhamad Eriq Ashari; Haryo Dwito Armono (Rekayasa, 2023)
The construction of the 150 kV Transmission electricity infrastructure by PT PLN (Persero) is an assignment from the Government in order to support electricity growth in Indonesia. Several 150 kV Transmission projects experienced delays in project completion due to inaccurate timing and project completion costs. The construction project of the 150 kV transmission involves engineering, procurement, construction, and commissioning activities, requiring careful calculations of time and costs while considering resources (Man, Material, Machine, and Method). The Critical Path Method (CPM) is used as the deterministic analysis approach for time analysis, while the Time Cost Trade-Off (TCTO) method is employed when there is a potential for project delays, acceleration, or cost overrun. The combination of the CPM and TCTO methods is suitable for project activities that are precisely known, while considering both parallel and serial work. Based on the research results, the 150 kV transmission project has 13 critical paths. The acceleration scheme that significantly impacts time and cost is the acceleration during the construction phase, and changes in all resource variables (Man, Material, Machine, and Method) affect both time and cost. However, a change in a single resource variable, namely Method, may impact time but not necessarily cost.